SOCIALIZATION OF PUBLIC INFORMATION GOVERNANCE OF VILLAGE GOVERNMENT HUMAN RESOURCES MANAGEMENT IN PAKUNCEN VILLAGE, BOJONEGARA SUB-DISTRICT - Eli Apud Saepudin; Rizki Amalia Nugraheni; Selfi Rindiani; Julia Rahmawati; Dellia Septia Ningrum; Adip Ekayasa Rukmana; Ria Maulana (Yayasan Education and Social Center, 2023)
The right of the people to be guaranteed to obtain public information in order to increase their active role in state administration, both at the level of supervision, implementation of state administration and at the level of involvement during the public decision-making process. The government's obligation is to provide information to the public quickly, easily, and accurately. In the KKM Student Work Lecture activity group 21 invited a lecturer from Universitas Bina Bangsa, Eli Apud Saepudin as a speaker in student activities in the field of human resource management of government, especially village government, in the Pkm Community Service activity Eli Apud Saepudin provided material with the theme Socialization of Public Information Governance of human resource management in the field of village government in Pakuncen village, Bojonegara sub-district which refers to the main Law Number 14 of 2008 concerning public information disclosure